A Rare Case of ARDS Caused by Bupropion Inhalation and Treated with Noninvasive Ventilation - Yousif Al-Saiegh; Jenna Spears; Pieter S. De Klerk; Joshua Hitchings; Christopher Lee; Tamara Mahr (Case Reports in Critical Care)
Acute respiratory distress syndrome, characterized by the Berlin criteria, is associated with a high mortality rate. Its treatment includes addressing the underlying etiology, general supportive measures, and achievement of effective oxygenation. New key data indicates that in a subset of patients, noninvasive ventilation techniques can be a therapeutic and equivalent alternative to traditional invasive ventilation. We present a rare case of ARDS triggered by nasal bupropion inhalation and effectively treated with noninvasive positive pressure ventilation resulting in complete resolution.